Acute effects of copper and mercury on the estuarine fish Pomatoschistus microps: Linking biomarkers to behaviour - Vieira, L. R.
The main objective of the present study was to investigate possible links between biomarkers and swimming performance in the estuarine fish Pomatoschistus microps acutely exposed to metals (copper and mercury). In independent bioassays, P. microps juveniles were individually exposed for 96 h to sub-lethal concentrations of copper or mercury. At the end of the assays, swimming performance of fish was measured using a device specially developed for epibenthic fish (SPEDE). Furthermore, the following biomarkers were measured: lipid peroxidation (LPO) and the activity of the enzymes acetylcholinesterase (AChE), lactate dehydrogenase (LDH), glutathione S-transferases (GST), 7-ethoxyresorufin-O-deethylase (EROD), superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR) and glutathione peroxidase (GPx). LC50s of copper and mercury (dissolved throughout metal concentrations) at 96 h were 568 μg L−1 and 62 μg L−1, respectively. Significant and concentration-dependent effects of both metals on swimming resistance and covered distance against water flow were found at concentrations equal or higher than 50 μg L−1 for copper and 3 μg L−1 for mercury (dissolved throughout metal concentrations). These results indicate that SPEDE was efficacious to quantify behavioural alterations in the epibenthic fish P. microps at ecologically relevant concentrations. Significant alterations by both metals on biomarkers were found including: inhibition of AChE and EROD activities, induction of LDH, GST and anti-oxidant enzymes, and increased LPO levels, with LOEC values ranging from 25 to 200 μg L−1 for copper and from 3 to 25 μg L−1 for mercury (dissolved throughout metal concentrations). Furthermore, significant and positive correlations were found between some biomarkers (AChE and EROD) and behavioural parameters, while negative correlations were found for others (LPO, anti-oxidant enzymes and LDH) suggesting that disruption of cholinergic function through AChE inhibition, decreased detoxification capability due to EROD inhibition, additional energetic demands to face chemical stress, and oxidative stress and damage may contribute to decrease the swimming performance of fish. Since a reduced swimming capability of fish may reduce their ability to capture preys, avoid predators, and interfere with social and reproductive behaviour, the exposure of P. microps to copper and/or mercury concentrations similar to those tested here may decrease the fitness of wild populations of this species.